Anticholinergic/Sedative Drug Burden and Subjective Cognitive Decline in Older Adults at Risk of Alzheimer's Disease. (4th September 2020) - Margolis, Seth A; Kelly, Dana A; Daiello, Lori A; Davis, Jennifer; Tremont, Geoffrey; Pillemer, Sarah; Denby, Charles; Ott, Brian R
Abstract: Background: Anticholinergic/sedative drug use, measured by the Drug Burden Index (DBI), has been linked to cognitive impairment in older adults. Subjective cognitive decline (SCD) may be among the first symptoms patients with Alzheimer's disease (AD) experience. We examined whether DBI values are associated with SCD in older adults at risk of AD. We hypothesized that increased DBI would be associated with greater SCD at older ages. Method: Two-hundred-six community-dwelling, English-speaking adults (age = 65 ± 9 years) at risk of AD (42% apolipoprotein ε4 carriers; 78% with AD family history) were administered a single question to ascertain SCD: "Do you feel like your memory is becoming worse?" Response options were "No"; "Yes, but this does not worry me"; and "Yes, this worries me." DBI values were derived from self-reported medication regimens using older adult dosing recommendations. Adjusting for relevant covariates (comorbidities and polypharmacy), we examined independent effects of age and DBI on SCD, as well as the moderating effect of age on the DBI-SCD association at mean ± 1 SD of age. Results: Both SCD and anticholinergic/sedative drug burden were prevalent. Greater drug burden was predictive of SCD severity, but age alone was not. A significant DBI*Age interaction emerged with greater drug burden corresponding to more severe SCD among individuals age 65 and older. Conclusion: Anticholinergic/sedative drug exposure was associated with greater SCD in adults 65 and older at risk for AD. Longitudinal research is needed to understand if this relationship is a pre-clinical marker of neurodegenerative disease and predictive of future cognitive decline.